Mechanism of Selective Ion Removal in Membrane Capacitive Deionization for Water Softening - Wang, Li; Lin, Shihong (Environmental science & technology, 2019)
Capacitive deionization (CDI) is an emerging technology capable of selective removal of ions from water. While many studies have reported chemically tailored electrodes for selective ion removal, the selective removal of divalent cations (i.e., hardness) over monovalent cations can simply be achieved using membrane CDI (MCDI) equipped with ion exchange membranes (IEMs). In this study, we use both experimental and modeling approaches to systematically investigate the selective removal of Ca2+ over Na+. Specifically, the impacts of current density, hydraulic retention time, and feed composition on the selectivity of Ca2+ over Na+ were investigated. The results from our study suggest a universal correlation between the ratio of molar fluxes and the ratio of spacer channel ion concentrations, regardless of operating conditions and feed composition. Our analysis also reveals inherent and universal trade-off relationships between selectivity and the Ca2+ removal rate and between selectivity and the degree of Ca2+ removal. This fundamental understanding of the mechanism of selective ion removal in MCDI can also be applied to flow-electrode CDI processes that employ IEMs.